Nest-site choice by loggerhead sea turtles as a risk-management adaptation to offset hatching failure by unpredictable storms and predators - Cassill, Deby L.; Watkins, Alison (Frontiers in Ecology and Evolution, 2022)
Abstract Along the coasts of Florida, United States, the nesting season of the loggerhead sea turtle, Caretta caretta, overlaps with the hurricane season. Nesting loggerhead females do not extend parental protection beyond depositing eggs in sandy, subterranean nests in locations that must provide a viable range of temperatures, moisture, and respiratory gas exchange. Thereafter, a female’s clutches are subjected to the uncertainties of desiccation, predation, flooding, or beach erosion. Here, using data from a 1996-2004 study of 94 tagged loggerhead females nesting on a small barrier island off the Gulf Coast of south Florida, United States, we show that breeding year and breeding month accounted for 81.8% of variation in hatching success; nest site choice explained the remaining 19.2%. We tested the hypothesis that the distribution of nest sites by loggerhead females was a randomized response to unpredictable hatching failure. We found that the emergence site along the beach-length axis, nest site choice along the beach-width axis, and distances between nest locations did not fit a uniform-random distribution or a normal distribution. Instead, we show that loggerhead females employed a “Goldilocks” distribution of nest sites—not too clustered nor too dispersed within a breeding season. Moreover, across multiple breeding seasons, loggerhead females selected nest sites along the beach with little-to-no-overlap with nest sites from previous breeding seasons. We propose that nest site choice by this population of loggerhead females constitutes a significant risk-management adaptation that deserves thoughtful consideration as we continue to assess the impacts of climate change on the future of loggerhead sea turtles.